PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN IPS - Lilis Lisdiati (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2020)
This research is motivated by the low student learning outcomes in social studies subjects was still in low category. The research objective was to improve the learning outcomes of social studies subjects for class IX-A students of SMP Negeri 2 Sidamulih through the use of the Problem Based Learning (PBL) model. This study used CAR method that was carried out in 2 cycles, each cycle consists of 2 meetings. The research subjects were 27 students of class IX A SMP Negeri 2 Sidamulih in the 2018/2019 academic year, consists of 16 male and 11 female student. The results of the research in cycle I showed that the average learning outcomes Increased 7,41% from 63,33 to 71,11 from the first meeting with a percentage of 25.93% at the second meeting, in Cycle II the average score was 78, 52 with a percentage of 74.07% at meeting 1 to 87.78 with a percentage of 96.30% at meeting 2. The results of skills in the first cycle increased on average from 68.75 with a percentage of 7% at meeting 1 to 76.16 with 33% percentage at meeting 2, in cycle II increased from 79.63 with a percentage of 70% at meeting 1 to 85.65 with a percentage of 93% at meeting 2.Based on the percentage of completeness, it can be concluded that the implementation of the Problem Based Learning model can improve student learning outcomes class IX A subject matter at SMP Negeri 2 Sidamulih.